Analisis kesulitan pada pembuktian teorema KPK dan FPB mahasiswa Tadris Matematika semester tiga kelas B UIN Malang - Salima, Syirtu Fillaili (Maliki Interdisciplinary Journal, 2024)
Number theory is a branch of mathematics that studies the properties, relationships, and types of parts of numbers. It should be noted that the aim of the lecture is that students are expected to study number theory to have the ability to prove a statement or proposition in mathematics. In the ability to prove this, of course, it takes some ability to think such as the ability to solve problems. This study focused on the ability to prove theorems mathematically in the Number Theory course with FPB and KPK materials by third semester students of the B class program of Mathematics Tadris UIN Maulana Malik Ibrahim Malang, which took a sample of 13 students from a total of 30 students. The results showed that of the 13 selected samples, 23.1% of students stated that they had no problems in proving a theorem, while 76.9% of students stated that they had some problems. This data shows that the ability of class B students of the Mathematics Tadris study program at UIN Maulana Malik Ibrahim Malang in proving a theorem on the FPB and KPK materials is still relatively low. This will be used as the basis for the evaluation of learning.